Relationship between water quality and land use at different spatial scales: A case study of the Mun River basin, Thailand - Hao Yu Tian (2020)
© 2020 Editorial Board of Journal of Agro-Environment Science. All rights reserved. Analyzing the relationship between land use and water quality at different spatial scales is of great value for understanding the causes and trends of water environment changes and promoting restoration and protection of the basin ecosystem. Taking the Mun River basin in Thailand as the research object, GIS, Moran 's I, and Spearman correlation analysis were used to explore the spatial distribution and differences in water quality and the response of water quality to land use patterns at different spatial scales. The results showed that in the past 20 years(1977—2017), the Moran 's I values of dissolved oxygen, biochemical oxygen demand, total phosphorus, nitrate nitrogen, ammonia nitrogen and suspended solids were 0.86, 0.38, 0.35, 0.40, 0.45, and 0.50, respectively, thereby showing significant spatial aggregation in the basin. Meanwhile, the Moran 's I values of total coliform bacteria and fecal coliform bacteria were - 0.15 and - 0.10, respectively, thereby showing discrete spatial patterns. The relationship between river water quality and land use is generally consistent at different spatial scales, but discrepancy exists in the relevance. The land use pattern at the buffer zone scale can better explain the water quality change in the Mun River basin; the relationship between water quality indicators and land use at the 5 km buffer scale is more significant. The relevant analysis results show that agricultural land and urban construction land act as a source of the water quality pollution load, while forest land intercepts and absorbs pollutants. Therefore, the water environmental protection in the Mun River basin should be based on non-point source pollution control, and focus on strengthening the control of fertilizers in agricultural production processes and controlling the direct discharge of pollutants such as domestic sewage into the river.